The Quality of Buffalo Sperm in Tris Egg Yolk Diluent with Addition of Different Levels of Mangosteen Peel Extract - Yendraliza, Yendraliza; Priyandi, Ahmad; Handoko, Jully; Sianturi, Ria Sari Gail; Kusumaningrum, Diana Andrianita (Jurnal Medik Veteriner, 2023)
This study aimed to determine the quality of buffalo sperm in tris egg yolk diluent added with mangosteen peel extract at different levels. This study was conducted using an experimental method using a completely randomized design consisting of four treatment concentrations of mangosteen peel extract (T1: 0%, T2: 5%, T3: 10%, and T4: 15%) and four replications, respectively. Parameters observed were motility, abnormalities, intact plasma membrane, and acrosome intact. In the results, the addition of mangosteen peel extract had a significant effect (p > 0.05) on the motility of buffalo sperm that had been diluted in egg yolk tris diluent. This study concluded that the addition of 5–10% mangosteen peel extract in egg yolk tris diluent has a significant effect on sperm motility, could minimize the abnormality, and minimize the decrease in the intact plasma membrane of the buffalo sperm.